AN ANOXIC INTRAPLATFORM BASIN IN THE MIDDLE TRIASSIC OF LOMBARDY (SOUTHERN ALPS, ITALY): ANATOMY OF A HYDROCARBON SOURCE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
The Ladinian rocks of Central Lombardy consist of carbonate platforms (Esino Formation) subdivided by intraplatform troughs represented either by dark, well bedded limestones, marls and dolomites of poorly oxic to anoxic environment (Perledo-Varenna and Lierna Formations), or by grey nodular cherty limestones (Buchenstein Formation). Subsidence and deposition rates were high ( >100 m/MA), both on the carbonate platform and in the anoxic intraplatform troughs. Sedimentological study of the anoxic intraplatform rocks in the Grigne Mountains has identified 12 main lithofacies with mudstone/ wackestones, both massive and laminated, forming more than 2/3 of the total thickness. Packstones and carbonate breccias, all originating or fed from the neighbouring shallow carbonate platforms, represent 6 % of the total thickness in the basin. Also the dominating micrite is thought to have originated by overproduction on the carbonate platform. Concerning the depositional processes, almost 3/4 of the total thickness is interpreted x re-sedimented. Dolomitization is widespread in the marginal parts of the basin. No benthonic macrofauna is present, and only sporadically the bottom oxygen content was sufficient to support a non skeletal infauna. Two depositional sequences have been detected, both causing emersion on the carbonare platform. The younger emersion was severe and the platform/basin system ceased to exist. The Grigne Mountains are presently arranged in three main tectonically stacked sheets. Vitrinite Reflectance, Illite Crystallinity Index, and Conodont Alteration Index, all suggest an increase of temperature within the sheets, from south to north, i.e. from the geometrically deeper to the more elevated, which has reached the field of deep diagenesis or even anchimetamorphism.
Keywords: Triassic; Lombardy; Italy; carbonate platform; organic matter.